Documenting “Meaning”: A Participant Model For Tangible Heritage Documentation By Social Media - Töre, Tigin; TÖRE, EVRİM ÖZKAN (UNESCO, 2013)
In this study it is proposed that collecting and sorting data produced by social media users will reveal the embedded footprints of social media on cultural heritage. This output should reveal the “meaning” or documenting the intangible attributes of the cultural heritage as a space. An application-service is proposed for connecting social platform posts with spatial attributes of heritage. The URL of the post will be sent to this application in order to be tagged and connected to relevant space. An information, idea or experience produced any time can be connected with the context of space. This connection will be saved in database convenient for filtering, reproducing and experiencing. Application also connects with this database, displays the relevant tags and rates the posts while visiting the heritage. This database produced by users; popular or unpopular spaces, experiences and ideas will be available for use of input for the decision making processes about the conservation and management of the cultural heritage.
Keywords: cultural heritage; digital heritage; social media; space; participation